Examining the policy narratives and the role of the media in policy responses to the COVID-19 crisis in Indonesia - Apriliyanti, Indri Dwi; Utomo, Wisnu Prasetya; Purwanto, Erwan Agus (2022)
This paper aims to investigate the related narratives presented in the media and their role in influencing the policy-making process related to the COVID-19 response in Indonesia. This study is based on the content analysis of online news and in-depth interviews with the political advisors of the president and the minister as well as the public health experts invited into the core group of policymakers. The analysis of the narrative policy framework revealed a relationship between the government’s response and the changing tone of media coverage. The study also found that the media has become an influential platform influencing policy agenda-setting. © 2021 Informa UK Limited, trading as Taylor & Francis Group.